Visual analysis of alpine meadow research trends and hotspots based on VOS viewer - Lin, Weishan; De, Kejia; Wei, Xijie; Wang, Wei; Zhang, Lin; Xiang, Xuemei; Li, Fei (Frontiers in Environmental Science, 2023)
Alpine meadows are the main vegetation type widely distributed on the Qinghai-Tibet Plateau and are of great importance to the Qinghai-Tibet Plateau and even the global grassland ecosystem. Bibliometrics is a popular interdisciplinary scientific field that analyses literature data through mathematical and statistical methods. It analyses and assesses the quality and interest of research and represents the current status and development of a specific field. We used VOS viewer software to visually analyse the literature related to alpine meadow research, and searched 3607 papers in the web of science core from January 1, 2000 to December 31, 2021. The terms "enzymes", "climate change", and "microorganisms" are the current hot topics in alpine meadow research. Therefore, alpine meadow research requires international cooperation and exchange, and diversified and multidisciplinary research has replaced single-disciplinary research as a trend in academic research today.